Donor-acceptor truxene-based porous polymers: synthesis, optoelectronic characterization and defense-related applications - Mendez-Gil, Nayara; Gámez-Valenzuela, Sergio; Echeverri, Marcelo; Suyo, Gary H.; Ruiz-Delgado, María del Carmen; Gómez-Lor, Berta (Wiley, 2024)
Four donor-acceptor (D-A) polymers are synthesized by combining two different electron donors (truxene and its more electron rich triaza analogue, triindole) with an electron-deficient monomer (benzothiadiazole) through two different positions (2,7,13 or 3,8,13) and their optoelectronic properties are studied by theoretical and experimental methods. One of the polymers exhibits remarkable sensing capabilities for explosive nitraoaromatics while another demonstrated efficient photocatalytic activity in the aerobic sulfoxidation of the sulfur mustard simulant 2-chloro-ethyl ethyl sulfide (MGS) sulfoxidation. These results highlight their potential applications in defense-related areas. Moreover, the structure-performance relationships observed among the four polymers have enabled us to deepen the understanding of the mechanisms underlying the performance of these polymers in the aforementioned applications, thereby providing valuable insights to further improve their properties.
Funding for open Access charge: Universidad de Málaga / CBUA. This research was funded by MICINN/AEI/ 10.13039/501100011033 (project PID2022-139548NB-I00, PID2019-104125RB-I00, and PID2020-112590GB-C22) and by Junta de Andalucía (P09FQM-4708 and P18-FR-4559). N.M.-G. and S.G.-V. contributed equally to this work. The authors would like to thank the computer resources, technical expertise and assistance provided by the SCBI (Supercomputing and Bioinformatics) center and the vibrational spectroscopy (EVI) lab of the Research Central Services (SCAI) of the University of Málaga
Keywords: Química física; Polímeros; Polímeros conductores; Polímeros - Propiedades eléctricas; Industria militar; Donor-acceptor (D-A) polymers; Electron donors; Polymers; Defense-related area